The Role of Prolactin as a Disease Activity Indicator in Some Rheumatic Diseases - Mohamed Ismail Abdelkarem; HM Fayed; Wael Abd El-Mohsen Abady; Eman Abulhagag Mohammed Mahmoud (SVU - International Journal of Medical Sciences)
Background: Autoimmune rheumatic diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and scleroderma, predominantly affect women and are characterized by systemic inflammation, leading to organ failure. Prolactin (PRL), a hormone produced by the pituitary gland and lymphocytes, significantly affects immune regulation and is implicated in the pathophysiology of these diseases. Objectives: This study aimed to evaluate the relationship between PRL levels and disease activity in RA, SLE, and scleroderma. Patients and methods: A cross-sectional case-control study involved 150 premenopausal women (50 with RA, 30 with SLE, and 20 with scleroderma) and 50 age-matched healthy controls. Clinical disease activity assessments (DAS28 for RA, SLEDAI for SLE, and MRSS for scleroderma) and laboratory estimation of serum PRL level were conducted. Results: The mean PRL levels in RA (26.17 ng/ml), SLE (25.23 ng/ml), and scleroderma (32.07 ng/ml) were significantly higher than controls (15.48 ng/ml) (P < 0.001). 42% of RA patients, 30% of SLE patients, and 50% of scleroderma patients had elevated PRL levels. Hyperprolacinemia is correlated with disease activity (DAS28 (r = 0.493, p = 0.0001), SLEDAI (r = 0.546, p = 0.002), and MRSS (r = 0.893, p = 0.0001), respectively). Conclusion: Serum PRL levels were significantly elevated in RA, SLE, and scleroderma, which is consistent with disease activity scores. Regular monitoring may be necessary because of the potential of PRL to function as a marker of disease activity. The therapeutic potential of dopamine agonists in autoimmune diseases warrants further investigation, as they have the potential to reduce flare-ups and organ involvement.